PROTECTION AGAINST CADMIUM TOXICITY IN RATS BY METHIONINE - PRAKASH, R.; AGRAWAL, V. P.; TYAGI, MAHESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Protective effects of methionine has been recorded against cadmium poisoning in liver and blood. Riversibility of biochemical lesions on total carbohydrates. glycogen, protein, lipid and malonaldehyde in liver and haematological parameters viz. haemoglobin percentage, methamoglobin, total RBC and WBC count, SGOT and SGPT indicated its necrotropic function in rat. Mechanism of methionine action has also been discussed.